Fear of small numbers : an essay on the geography of anger - Appadurai, Arjun, 1949- (Public planet books., 2006)
Providing a conceptually innovative framework for understanding sources of global violence, this work describes how the nation-state has grown ambivalent about minorities at the same time that minorities increasingly see themselves as parts of powerful global majorities.